The New Testament in Antiquity and Byzantium - Houghton, H.A.G.,Parker, David C.,Strutwolf, Holger (De Gruyter, 2019)
Klaus Wachtel has pioneered the creation of major editions of the Greek New Testament through a blend of traditional philological approaches and innovative digital tools. In this volume, an international range of New Testament scholars and editors honour his achievements with thirty-one original studies. Many of the themes mirror Wachtel's own publications on the history of the Byzantine text, the identification of manuscript families and groups, detailed analysis of individual witnesses and the development of software and databases to support the editorial process. Other contributions draw on the production of the Editio Critica Maior, with reference to the Gospels of Mark and John, the Acts of the Apostles, the Pauline Epistles and the Apocalypse. Several chapters consider the application of the Coherence-Based Genealogical Method. A wide selection of material is considered, from papyri to printed editions. The Greek text is analysed from multiple perspectives, including exegesis, grammar and orthography, alongside evidence from versions in Latin, Syriac, Coptic and Gothic. This collection provides new insights into the history of the biblical text and the creation, development, analysis and application of modern editions.
10.1515/9783110591682
Keywords: Festschrift; Griechisch; Textgeschichte; Redaktion; Edition